Dose profile surrounding a waste repository - Parson, Jenelle, author; Brandl, Alexander, advisor; Johnson, Thomas, committee member; Woody, Robert, committee member (Colorado State University. Libraries, 2014)
The waste repository analyzed is an interim storage facility that houses low and intermediate level conditioned radioactive waste. In total, it contains 9996 200-L waste barrels. The barrels are arranged in a crate geometry to ensure easy access to each barrel. The repository walls are 0.2 m thick with extra shielding (0.7 m) present on the west, north, and east sides of the repository. Instead of extra shielding the south side of the repository has a 5.25 m gap from the crates to the wall, allowing for crane maneuverability. The dose rate profile was analyzed using Monte Carlo N-Particle Transport eXtended (MCNPX) for the south, west, and north sides. The east side was not explicitly analyzed, because of the symmetry between the west and east sides. The dose rate was analyzed using f5 detector tallies and fluence rate to dose rate conversion factors from ICRP 21. Here, contributions due to skyshine and other wall effects are analyzed in detail. For the west and north side (where shielding was present), it was found that as distance from the source increases the dose rate initially increases logarithmically to a maximum and subsequently falls off following an exponential function. The initial increase in dose rate is significant with a peak dose rate as much as 300% of the dose rate at the wall and remaining elevated until approximately 60 m from the waste repository. A similar dose rate increase is not observed for the southern side of the repository; instead, the dose rate falls off with a power function corresponding to a function between that for an infinite plane and a point source. The dose rate profile was analyzed with and without repository structures, and the initial increase is only present with the repository structure. This indicates that the initial rise is due to the presence of walls and/or roof. The shape of the dose rate profile closely follows observed skyshine functions at accelerator facilities. Skyshine and wall effects have been analyzed extensively for medical accelerator facilities, but are generally not considered for a waste repository; the work suggests that skyshine and wall effects may be more significant than previously thought and should be considered in the design and construction of waste repositories.
Keywords: dose rate; health physics; MCNP; modeling; radiation; waste repository